Ghrelin treatment induces rapid and delayed increments of food intake : A heuristic model to explain ghrelin's orexigenic effects - Cornejo, María Paula (2021)
Ghrelin is a stomach-derived peptide hormone with salient roles in the regulation of energy balance and metabolism. Notably, ghrelin is recognized as the most powerful known circulating orexigenic hormone. Here, we systematically investigated the effects of ghrelin on energy homeostasis and found that ghrelin primarily induces a biphasic effect on food intake that has indirect consequences on energy expenditure and nutrient partitioning. We also found that ghrelin-induced biphasic effect on food intake requires the integrity of Agouti-related peptide/neuropeptide Y-producing neurons of the hypothalamic arcuate nucleus, which seem to display a long-lasting activation after a single systemic injection of ghrelin. Finally, we found that different autonomic, hormonal and metabolic satiation signals transiently counteract ghrelin-induced food intake. Based on our observations, we propose a heuristic model to describe how the orexigenic effect of ghrelin and the anorectic food intake-induced rebound sculpt a timely constrain feeding response to ghrelin.